Numerical simulation of film cooling over flat plate - Bahr Ennil, Ali S.; M. Elfaghi, Abdulhafid (Asian Research Publishing Network (ARPN), 2015)
The effect of film cooling over flat plate is investigated using the commercial CD code; Fluent 6.3. The computational domain includes the coolant supply tube as well as the main mixing region. A tube L/D of 4 and injection angles of (30o , 60o , and 90o ) were employed for blowing ratio of (0.33, 0.5, and 1.67), and a density ratio of 1.14. Adiabatic film cooling effectiveness distributions were also determined for inline and staggered arrangements. The main observation from this study that the 30o hole gave larger effectiveness values than 60o and 90o at the blowing ratio of 0.33 with the same length-to-diameter ratio. The maximum effectiveness was achieved with a blowing ratio of 0.5. The results show that the increase of blowing ratio negatively affects film cooling, such that for the blowing ratio of 1.67 the injected coolant tends to lift off from the wall due to the increase of the wall normal momentum. The comparisons for numerical results with experimental data are presented.